Siderophore Activity of Partially Acetylated Fusarinines from the Sponge-Derived Fungus Pseudogymnoascus Verrucosus - Chavez-Rosales, R (American Chemical Society, 2025)
Pseudogymnoascus is a fungal genus prevalent in Antarctica whose metabolism, including the types of siderophores it synthesizes, remains largely unexplored. In this work, we investigated the siderophores produced by Pseudogymnoascus verrucosus FAE27, a strain isolated from the Antarctic marine sponge Hymeniacidon sp., grown under iron-limiting conditions. Two new hydroxamate-type siderophores, N,N′-diacetyl-fusarinine B (7) and N-acetyl-fusarinine A (8), are described here as the first naturally occurring partially acetylated fusarinines to date, along with the known fusarinine (1) and five of its analogues: N-acetyl-fusarinine (2), N-acetyl-fusarinine-methylester (3), N,N′,N″-triacetyl-fusarinine C (4), N,N′-diacetyl-fusarinine A (5), and N,N′,N″-triacetyl-fusarinine B (6). A comprehensive NMR spectroscopic characterization of their Ga3+ complexes was conducted. Surprisingly, the full spectroscopic characterization of most of these known siderophores was either incomplete or absent in the literature. The analysis of 1H, 13C, and 2D NMR data provided significant structural insights, including the impact of Ga3+ coordination on chemical shifts. Additionally, the absolute configuration of the amino acid units in compounds 1-8 was determined via acid hydrolysis and Marfey’s analysis. Finally, the siderophore activity of all purified compounds was confirmed by their ability to promote fungal growth under iron-limiting conditions. © 2025 The Authors. Published by American Chemical Society and American Society of Pharmacognosy.